EKSPOR BRIKET ARANG TEMPURUNG KELAPA INDONESIA KE KOREA SELATAN TAHUN 2019-2020 (Studi Kasus: PT. Tom Cococha Indonesia di Jawa Barat) - Andari, Fiolina Putri; Retaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Coconut shell charcoal briquettes are a high value-added derivative of coconut cosmmodities, offering strong export potential and significant contributions to national foreign exchange earnings. This study investigates Indonesia’s export prospects for coconut shell charcoal briquettes in the international market, with a particular focus on South Korea—a country with one of the highest charcoal consumption rates in East Asia. The research centers on international trade activities for this product under the Harmonized System (HS) code 440290. A qualitative case study approach was employed, drawing on data from observations, in-depth interviews, literature reviews, and official sources such as Statistics Indonesia (BPS), UN Comtrade, and the International Trade Centre (ITC). The studi showed that Indonesian briquettes are highly competitive in the South Korean market due to their superior properties: high fixed carbon content, low ash levels, stable combustion, and environmentally friendly characteristics. Despite this advantage, significant challenges remain—particularly a shortage of raw materials driven by excessive raw coconut exports and insufficient national regulation governing supply for downstream industries. Additional constraints include logistical bottlenecks and limited shipping access. The study recommends assertive policy intervention to balance raw coconut exports with the development of value-added processing industries, thereby enhancing Indonesia’s position within the global alternative energy supply chain. Keywords: charcoal briquette, coconut shell, export, South Korea, alternative energy, international trade.